Ethics in the digital age: exploring the ethical challenges of technology - Rabiu, Aliyu Alhaji; Mohd Noor Merican, Ahmad Murad; Al Murshidi, Ghadah (IIUM Press, 2025)
This research paper delves into the ethical challenges arising from rapid technological advancements in the digital age, focusing on Islamic perspectives. It seeks to establish a comprehensive framework based on Islamic principles from the Qur'an, Hadith, and scholarly interpretations to guide human behaviour amidst these changes. While innovations like artificial intelligence, social media, and data analytics offer substantial benefits, they also present ethical dilemmas requiring careful consideration. The study examines challenges in areas such as privacy and surveillance, social media conduct, artificial intelligence, automation, and data security, exploring how Islamic ethics can guide individuals and communities in navigating these issues. Utilizing qualitative research methods, the study collects data from libraries, online sources, and researchers' experiences, which are then analysed to extract meaningful insights. By referencing relevant Qur'anic verses and authentic Hadiths, the study demonstrates the application of Islamic ethics to technological challenges. It explores various Islamic ethical frameworks, including maqasid al-shari’ah (objectives of Islamic law), fiqh al-mu'amalat (Islamic jurisprudence of transactions), and ijtihad (independent legal reasoning), to address these challenges. The paper recommends integrating Islamic ethical principles into educational curricula, professional codes of conduct, and technology-related policy frameworks. This integration is crucial for fostering ethical practices and decision-making, ensuring that technological advancements align with Islamic values and ethical standards. The study concludes that incorporating Islamic ethics into technology discussions enables individuals and societies to effectively navigate the digital age's challenges while upholding values that promote justice, truthfulness, and responsible conduct. It emphasizes the importance of understanding Islamic ethics in the context of the digital age to address contemporary ethical dilemmas and ensure that technological progress aligns with Islamic values.